2022
DOI: 10.1111/1462-2920.16211
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D and phosphatidic acid mediate regulation in the biosynthesis of spermidine and ganoderic acids by activating GlMyb in Ganoderma lucidum under heat stress

Abstract: Polyamines are essential for all kinds of organisms and take part in the regulation of multiple biological processes. Our previous study revealed that heat stress promoted the conversion of putrescine to spermidine and subsequently promoted the accumulation of ganoderic acids (GAs). However, how heat stress affects polyamine homeostasis remains unclear. To explore the underlying mechanism by which heat stress promoted spermidine biosynthesis, we assessed the effects of signalling molecules that respond to heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…GA was extracted and detected as previously described 22 . In brief, dried mycelial powder (200 mg) was ultrasonically extracted in 10 mL of 95% ethanol for 2 h. The mixture was centrifuged at 4000 rpm for 10 min to obtain the supernatant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GA was extracted and detected as previously described 22 . In brief, dried mycelial powder (200 mg) was ultrasonically extracted in 10 mL of 95% ethanol for 2 h. The mixture was centrifuged at 4000 rpm for 10 min to obtain the supernatant.…”
Section: Methodsmentioning
confidence: 99%
“…At present, based on developments in genomics and proteomics in recent years and the progress of genetic research methods, there are an increasing number of reports on the mechanism of GA biosynthesis. Previous reports have shown that signaling molecules (reactive oxygen, nitric oxide, calcium ions) and environmental factors (high temperature, nutrients, chemicals) in the GA biosynthesis play an important role in GA biosynthesis 22 28 , indicating that GA biosynthesis is driven by many factors coregulated. Importantly, research on these mechanisms is far from sufficient to reveal the regulatory network of the GA biosynthesis mechanism.…”
Section: Introductionmentioning
confidence: 99%